Effectiveness of Think-Pair-Share and STEM Models on Critical Thinking in Early Childhood Education - Syafruddin Syafruddin; Hasyim Mahmud Wantu; Abdul Muis; Ahmad Zain Sarnoto; Siti Fatimah Hiola; Ika Agustina; Tomi Apra Santosa; Unpris Yastanti; Aat Ruchiat Nugraha; Dewanto Dewanto; Everhard Markiano Solissa; Sukini Sukini; Andi Sri Rezky Wulandary; Makhrus Ali; Andri Kurniawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the effectiveness of the STEM-based Think Pair Share model on the thinking ability of early childhood education students.Â The research is a meta-analysis research. This study analyzed 17 primary studies that had met the established inclusion criteria. The data analysis in this study is statistical analysis. This study concluded thatÂ the analysis using the random effect model obtained the average effect size value (d= 0.972; p <0.001). This effect size is very high. These results show that the STEM-based Think Pair Share model strongly influences the critical thinking ability of prospective Early Childhood Education (PAUD) teachers compared to the traditional learning model.